Student Worksheet Based on Scientific Approach to ‎Improve Learning Outcomes and Creative Thinking Ability ‎of Elementary Student - Nurkholis, Akhmad (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2019)
The scientific approach is an approach that is much highlighted in the implementation of the 2013 curriculum with learner-centered learning. Learning steps with this approach is designed so that learners are actively building concepts, principles or laws through the stages which includes observing, asking, reasoning, trying, and forming networks. The aims of this study are to develop student worksheets with a scientific approach to ecosystem balance learning material, describe the effect of student worksheets based on a scientific approach toward creative thinking skills, and explain the effect of student worksheets with a scientific approach to student learning outcomes. The method used in this study was pre-experimental design with the research design of one-group pretest-posttest design. Subjects in this study were learners VB class Madrasah Ibtidaiyah Negeri/MIN (Islamic Elementary School) 1 Magelang which numbered 26 people. The data collection techniques used are interviews, observation and written tests. The results of the study show that the student worksheet based on the scientific approach can improve student learning outcomes of 4.50 from an average of 70.00 to 74.50, and increasing the number of students completeness by 8 from 14 to 22 students who completed, the percentage of completed students increased by 30.76%, from 53.85% to 84.61%, the class completeness percentage of 84.61% exceeded the class completeness criteria was set at 80%, and a positive effect on creative thinking skills of learners.